Analisis Laporan Realisasi Anggaran Pendapatan Dan Belanja Desa (APBDES) Desa Suato Lama Kecamatan Salambabaris Kabupaten Tapin Berdasarkan Ratio Financial Independence, Effectiveness, Efficiency Periode 2021-2023 - Sari, Riri Velina; Yusri, Yusri; Yanti, Sari; Novianty, Nadya (Politeknik Negeri Ambon, 2024)
This research aims to determine level of independence ratio, effectiveness ratio and efficiency ratio. Suato Lama Village finances based original village income and transfer income. A financial report is budget realization report prepared entity by presenting budget realization report based on basis specified in statutory regulations. There are differences results in three ratios, namely financial independence ratio, effectiveness and efficiency. Where results of very low level financial independence indicate that Suato Lama Village still very dependent on financial assistance from the central and regional governments to finance government administration, development and community empowerment activities. This type of research uses quantitative descriptive research. Data collection techniques in this research used documentation and interview techniques. Documentation technique used Suato Lama Village APBDes financial report for 2021-2023 budget. Technical data analysis used is financial ratio analysis. Based on financial ratio analysis, it can be concluded that performance Suato Lama Village Government for 2021-2023 fiscal year with independence ratio is still very low with average value of 1.85%. Financial performance Suato Lama Village Government for 2021-2023 fiscal year has been very effective with average value 108.01%. Financial performance Suato Lama Village Government for 2021-2023 budget year based on efficiency ratio stated to be quite efficient with average ratio 87.39%. In the independence ratio, it is stated that Suato Lama Village Government is still not optimal in managing village's original income sources. Meanwhile, effectiveness and efficiency ratio states that Suato Lama Village Government is able to carry out its duties in terms of realizing the village's original income.